2015
DOI: 10.1094/cchem-05-14-0099-r
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Structural, and Proteomic Analysis of Starch Granules from Maize Landraces of Northwest Mexico

Abstract: Cereal Chem. 92(3):320-326

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
(55 reference statements)
3
8
2
1
Order By: Relevance
“…Dent type kernels of L-3 and L-1 had significantly the lowest starch content and significantly the highest hardness whereas H-1 had significantly higher starch content and significantly the lowest hardness. These findings are in agreement with other studies that total starch content has a negative correlation with hardness (Pineda-Hidalgo et al, 2015). Amylose content varied from 18.6 to 22.1% (Table 4) as reported in other studies (Gayral et al, 2015).…”
Section: Chemical Propertiessupporting
confidence: 93%
“…Dent type kernels of L-3 and L-1 had significantly the lowest starch content and significantly the highest hardness whereas H-1 had significantly higher starch content and significantly the lowest hardness. These findings are in agreement with other studies that total starch content has a negative correlation with hardness (Pineda-Hidalgo et al, 2015). Amylose content varied from 18.6 to 22.1% (Table 4) as reported in other studies (Gayral et al, 2015).…”
Section: Chemical Propertiessupporting
confidence: 93%
“…(2019) and Pineda-Hidalgo et al (2015) in samples of maize from indigenous races, whose values ranged from 65.4-79.2 Â kg/hL and 73.8-76.6 Â kg/hL, respectively. This observed difference may be related to the grain moisture at the time of HW measurement or the higher content of vitreous endosperm, which may indicate greater hardness and starch content, providing higher quality to the LP.…”
Section: Physical Properties Of the Lpmentioning
confidence: 98%
“…A similar result to this work was observed in the study by Idikut et al (2012), who evaluated germination under different temperatures and salt concentrations, and found that the popcorn landraces had higher germination and vigor values than the seeds of commercial hybrid maize varieties. Landraces are described in the literature as being resistant to diseases, in addition to presenting good tolerance and adaptation to stressful abiotic conditions (Araújo et al, 2015;Idikut et al, 2012;Pineda-Hidalgo et al, 2015;Zulkadir & Ídikut, 2021). In terms of good performance, LP seeds are classified as vigorous (Marcos Filho, 1999), are stored in good conditions (packaging, temperature, and humidity), and can be used for propagation in the form of seeds, thereby exceeding the minimum required (70%) for commercialization in Brazil (Brasil, 2013).…”
Section: Physiological Properties Of the Lpmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] Early studies observed that the starch granules of soft maize grains are mainly spherical, whereas the starch granules of hard and intermediate hard maize grains are polygonal and compacted. [13] The spherical or ovoid shapes in inbred lines are mainly due to that the starch granule is loosely packed, whereas the angular form in hybrids is tightly packed within the endosperm cell. [6] This finding is also partially demonstrated, where the grains with less starch content are shrunken in inbred lines, while plump in hybrids [24] (Figure S2, Supporting Information).…”
Section: Introductionmentioning
confidence: 99%